Simplified mechanics and strength of materials - Ambrose, James (Hoboken, New Jersey : John Wiley & Son, Inc., 2002)
Requiring little in the way of mathematic ability, but providing much information, this guide shows readers how they can understand and predict how a building and its materials will perform when exposed to a variety of external forces (mechanics). New information in this edition includes an analysis of indeterminate structures and the ultimate strength resistance of those structures. A greater emphasis is also placed on the fundamentals, providing professionals with simple concise solutions to common structural problems. Updated code and technology information is included, as are many more ill
Structures: Purpose and function -- Forces and force actions -- Analysis of trusses -- Analysis of beams -- Continuous and restrained beams -- Retaining walls -- Rigid frams -- Noncoplanar force systems -- Properties of sections -- Stress and deformation -- Stress and strain in beams -- Compression members -- Combined forces and sresses -- Connections for structural steel -- Reinforces concrete beams
Includes index.
Keywords: MECHANICS, APPLIED